Co‐Infection, but Not Infection Intensity, Increases Shedding in a Gastrointestinal Helminth of Gamebirds - Katherine Prescott; Emile Michels; Barbara Tschirren (Ecology and Evolution)
ABSTRACT Host heterogeneity in disease transmission is commonly seen across host‐pathogen systems, and identifying individuals who contribute disproportionately to pathogen transmission (i.e., superspreaders) is key to understanding disease dynamics and managing outbreaks. It is often assumed that shedding intensity is directly proportional to infection intensity. However, theory predicts that co‐infection might modulate the relationship between infection intensity and shedding, promoting increased onward transmission. Here, we quantify the relative importance of infection intensity and co‐infection on shedding in Heterakis gallinarum, a gastrointestinal helminth of gamebirds, in a population of ring‐necked pheasants during the shooting season of 2023. We found that infection intensity was a poor predictor of shedding intensity. Instead, increased shedding was linked to co‐infections with other endoparasites. Hosts co‐infected with Syngamus trachea, Capillaria spp. and/or Eimeria spp. exhibited higher shedding intensity of H. gallinarum than those infected with H. gallinarum alone. This effect was additive, with each additional co‐infection further increasing H. gallinarum shedding. There were no sex differences in shedding, but male hosts had higher H. gallinarum infection intensities. Our results show that shedding intensity is not simply explained by infection intensity, but rather is the result of complex host–parasite and parasite–parasite interactions. This highlights the importance of considering such interactions in understanding disease emergence and persistence in natural populations.